A study on the strengths، weaknesses، opportunities and threats of Iranian smart schools - BiBi Eshrat Zamani; Bita Ghassab Pour; Jalal Jabal Ameli (فصلنامه نوآوری‌های آموزشی, 2010)
The main purpose of this study was to examine the strengths، weaknesses، opportunities and threats (SWOT) that Iranian smart schools were confronted with. Another purpose was conducting a comparison between SWOT of governmental and private smart schools. The research methodology was descriptive survey. To collect the required data، tworesearcher-made questionnaires were distributed among teachers and students. The questionnaires included questions on four domains of strengths، weaknesses، opportunities and threats (SWOT) with Likert scale and 5 multiple choice questions for demographic information. The research sample included 110 students and 77 teachers from four smartschools in Tehran city.Results of the study indicated that the average mean of four domains of SWOT were higher than average of 3 in both types of smart schools. This indicated that despite strengths and opportunities، there were weaknessesand threats in such schools. The most important strengths of these schools were increasing the teachers’ and students’ informational and media literacy and changing the teachers’ role from transmitter of information to afacilitator. Weaknesses and threats for these schools were lack of structure and appropriate culture for implementation and use of information and communication technologies in those schools. From the students’ point of view، the strengths and opportunities in private smart schools were more than governmental schools.